Histological and morphometric study of human placenta in hypertensive pregnant women in a tertiary care hospital in West Bengal-a cross-sectional study - Nabanita Chakraborty; Chunder, Rajasri; Priyanka Priyadarshini; Soham Chakraborty (Asian Journal of Medical Sciences, 2025)
Background: The placenta is a vital organ that develops during pregnancy and plays a critical role in fetal growth and development. It acts as a bridge between the maternal and fetal circulations, allowing for the exchange of nutrients, oxygen, and waste products. The placenta also produces hormones and growth factors necessary for fetal development and prepares the fetus for extrauterine life. Hypertensive disorders of pregnancy are a major cause of maternal and fetal morbidity and mortality. Aims and Objectives: To study the histological and morphometric changes of human placenta in hypertensive pregnant women in a tertiary care hospital in West Bengal. Materials and Methods: A cross-sectional study was conducted with placenta from 60 hypertensive pregnant mothers and 60 pregnant mothers with uncomplicated pregnancy from the Department of Obstetrics and Gynaecology, Jagannath Gupta Institute of Medical Sciences and Hospital, Budge Budge, West Bengal. The gross morphological and histological examination of placentae was done in the Department of Anatomy. Results: The mean age of hypertensive mothers was 26.5±3.5295 years, which was slightly higher than that of nonhypertensive mothers (24±3.3446 years). The placental weight, diameter and thickness were reduced in the hypertensive mothers. The hypertensive placentae showed higher incidence of fibrin deposition (33%), syncytial knots (23%), infarction (20%). Stromal fibrosis and villous obstruction were found in hypertensive placenta only. Conclusion: During pregnancy significant histomorphological changes in placenta are caused due to hypertensive disorders which lead to harmful and severe fetal outcomes. A valuable insight into the mechanism of placental dysfunction can be achieved through a detailed examination after delivery.